Spontaneous Iliopsoas Muscle Hemorrhage Secondary to Ibrutinib (Imbruvica; Pharmacyclics): Brief Report. (5th May 2016) - Sarcon, Anna; Botta, Gregory P.; Patel, Nikunj; Saven, Alan
Ibrutinib (Imbruvica; Pharmacyclics) is the first Food and Drug Administration–approved inhibitor of Burton's tyrosine kinase (BTK). Attenuation of BTK signaling ultimately leads to inhibition of B-cell proliferation and apoptosis. After a series of clinical trials, the Food and Drug Administration approved ibrutinib in patients with relapsed chronic lymphocytic leukemia in 2014 and Waldenström's macroglobulinemia in 2015. Those trials included rare grade 3+ hemorrhagic events associated with ibrutinib. Herein, we report a unique presentation of back pain due to iliopsoas muscle hemorrhage in a patient with Waldenström's macroglobulinemia after initiation of ibrutinib.